2005
DOI: 10.1021/la047317n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Film-Forming Conditions on Surface Properties and Structures of Diblock Copolymer with Perfluoroalkyl Side Chains

Abstract: Film-forming conditions (cast solvents and film-forming technique: casting or spin-coating) are found to regulate the surface free energy of a diblock copolymer composed of methyl methacrylate and 2-perfluorooctylethyl methacrylate (PMMA-b-PFEMA). The surface properties and structures both in the solid state and in the solution of this polymer were investigated using dynamic contact angle, X-ray photoelectron spectroscopy, X-ray diffraction, reflection-adsorption Fourier transform infrared spectroscopy, dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 30 publications
(50 reference statements)
4
74
0
3
Order By: Relevance
“…The d-spacing calculated from the peak position was ca. 0.50 nm, which was close to the intermolecular distance between helical chains of PTFE hexagonal (d ¼ 0:49 nm) [38][39][40][41] and was almost the same as the intermolecular distance between R f groups at the side chains of PFA-C 8 spin cast films (d ¼ 0:50 nm). Therefore, it was suggested that the rigid rod-like R f groups underwent hexagonal packing in the brush films of PFA-C 8 with thicknesses of 11 and 43 nm.…”
supporting
confidence: 63%
“…The d-spacing calculated from the peak position was ca. 0.50 nm, which was close to the intermolecular distance between helical chains of PTFE hexagonal (d ¼ 0:49 nm) [38][39][40][41] and was almost the same as the intermolecular distance between R f groups at the side chains of PFA-C 8 spin cast films (d ¼ 0:50 nm). Therefore, it was suggested that the rigid rod-like R f groups underwent hexagonal packing in the brush films of PFA-C 8 with thicknesses of 11 and 43 nm.…”
supporting
confidence: 63%
“…These results indicate that the polymer films have a fluorine-rich surface and the carbon-rich interior. [21,22] The larger F/C ratio value at the take-off angle of 308 compared to that at 908 also suggests that the CF 3 terminated polymers are fluorine enriched at the outermost surface. [23] The NEXAFS analysis indicated the alignment of the CF 3 end group and hydrocarbon in the side chain at the surface of the CF 3 -8SE and CF 3 -10SE films.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the inherent non-stick behavior fluorinated polymers are candidates as lubricant, wear control, antisoiling and anti(bio)fouling materials. [8][9][10][11][12][13][14][15] In this work, we synthesized welldefined poly(styrene-b-2-perfluorooctylethyl acrylate) copolymers, in order to study how the different chemical composition can affect the bulk and surface properties of the polymeric films. The liquid crystalline copolymer with the shortest fluorinated block was then incorporated into blends with a commercial thermoplastic elastomer SEBS.…”
Section: Introductionmentioning
confidence: 99%